Diversidade de cepas produtoras de betalactamases de espectro estendido em um hospital público de Boa Vista-RR - Brandão, Márcia Brazão e Silva (2018)
The emergence of antimicrobial resistant bacteria is occurring all over the world at a faster rate than the discovery of new drugs, putting their registration at risk. Bacteria of the extended-spectrum beta-lactam-producing Enterobacteriaceae (ESBL) are widely disseminated in hospital settings. The incorrect disposal of clinical waste in hospital effluents, allowing the antimicrobial resistance clinics to be more recent and demonstrate environmental risk insofar as they allow the dissemination of this resistance. This research was presented with a series of information that characterized the antimicrobial agents in clinical strains and a picture with the presence of hospital nurses, the faces followed, the dissemination of pathogenic microorganisms in the environment. The aim of this research is to characterize a diversity of hospital strains of the General Hospital of Roraima (HGR) comparing them with health clinics without the same hospital and to conduct a survey of resistance genes of the families: TEM, SHV and CTX, responsible for ESBL coding and hydrolysis to antimicrobials of the class of cephalosporins, penicillins and monobactans. For the proposed proposal, we included the clinical data of patients hospitalized in the HGR and collected hospital septic tank samples in a period of June 2014 in June 2016 in a molecular study to identify resistance genes through the chain reaction polymerase chain reaction (PCR) and sequencing test by the Sanger method. The results showed greater clinical relevance regarding the detection of ESBL, were of urine samples, catheter tip, tracheal secretion and blood. The resistance profile in samples from patients and children is identified as piperacillin / tazobactam, imipenem and amikacin as the most sensitive drugs for ESBL-producing bacteria, as well as the predominance of Klebsiella sp. Among the problems of the TEM gene among the coding of beta-lactamases. ESBL genes were identified in frequencies and isolated and in combination. A characterization of the ESBL subtypes evidences a presence of the CTX-M-15 gene, more frequent worldwide, besides the presence of the SHV gene and the TEM-181 gene in Effluent strains. The results indicate a wide dissemination of the ESBL genes in the clinical strains and in the effluent of HGR.